2017
DOI: 10.3329/ajmbr.v2i4.31002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of enteric bacteria in the popular street food chotpoti in Dhaka, Bangladesh

Abstract: Contaminated street food has been linked to food-borne illness and food-borne outbreak. Chotpoti is a popular street food in Bangladesh. This study was conducted to identify enteric bacteria in chotpoti sold in different parts of the capital city Dhaka. From July to October, 2012 we purposively selected 18 sites where chotpoti was sold in Dhaka city. From each site we randomly selected six chotpoti stalls for sample collection. At each stall we aseptically collected approximately 100 gm of a combined sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In addition, Biswas, Parvez, Shafiquzzaman, Nahar, and Rahman (2010) and Yannick, Rawlings, & Emmanuela (2013) reported the presence of E. coli in RTE meat from Bangladesh (Asia) and Cameroon (Central Africa), respectively, whereas diarrheagenic E. coli strains were recovered from grilled chicken in Burkina Faso (West Africa) (Somda et al, 2018). Similarly, Pseudomonas was detected in street-vended juice in Pakistan, (Batool, Tahir, Rauf, & Kalsoom, 2013), whereas in Bangladesh (Asia) and Ethiopia, Klebsiella was found to contaminate chotpoti and ambasha, respectively (Eromo, Tassew, Daka, & Kibru, 2016;Hassan et al, 2016).…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…In addition, Biswas, Parvez, Shafiquzzaman, Nahar, and Rahman (2010) and Yannick, Rawlings, & Emmanuela (2013) reported the presence of E. coli in RTE meat from Bangladesh (Asia) and Cameroon (Central Africa), respectively, whereas diarrheagenic E. coli strains were recovered from grilled chicken in Burkina Faso (West Africa) (Somda et al, 2018). Similarly, Pseudomonas was detected in street-vended juice in Pakistan, (Batool, Tahir, Rauf, & Kalsoom, 2013), whereas in Bangladesh (Asia) and Ethiopia, Klebsiella was found to contaminate chotpoti and ambasha, respectively (Eromo, Tassew, Daka, & Kibru, 2016;Hassan et al, 2016).…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…In this research, E. coli was isolated at a rate of 8%. In a previous study (Hassan et al, 2016) a lower incidence of 3% (n=84) E. coli strains were found in the street food chotpoti (3%, n=84). Kharel et al (2016) found E. coli in a variety of street food samples, including pakodas, and samosas.…”
Section: Prevalence Of E Coli In Food Samplesmentioning
confidence: 73%
“…Inadequate food safety knowledge and proper personal hygiene practices along with lack of public awareness are responsible for increasing foodborne disease burden in developing countries (Birgen et al, 2020). Contaminated street food has been related to foodborne illness and foodborne outbreaks equally (Hassan et al, 2016). Therefore, foodborne infections have become a rising public health concern and an alarming issue worldwide, which cause up to 2 million deaths in unindustrialized countries each year (Rahman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to inexpensiveness, unique flavor, variation and other conveniences the demand for street vended foods is increasing among urban people [1]. There are about 200,000 street food vendors in Dhaka city alone and the number is growing due to rapid urbanization [2,3]. Most vendors set up their stalls near bus terminals, busy roads, in front of schools, markets and railway stations in hopes of high potential customers.…”
Section: Introductionmentioning
confidence: 99%
“…Most vendors set up their stalls near bus terminals, busy roads, in front of schools, markets and railway stations in hopes of high potential customers. Vending carts are also placed by the side of municipal drains and sewage which attract insects and flies [2]. All these places have limited access to basic sanitary facilities such as running water, garbage disposal and clean toilets which puts the cleanliness of food preparing places and personal hygiene of vendors in question [4].…”
Section: Introductionmentioning
confidence: 99%